Adventure and imagination - 20160731 frey50; Wilhelm, Hans, 1945-; Heling, Kathryn; Hembrook, Deborah; Davidson, Ellen Dee, 1954-; Richardson, Bill, 1955-; Shulman, Mark, 1962-; Coulman, Valerie, 1969-; Findaway World, LLC.; TumbleBook Library; Playaway View. ([Solon, Ohio] : Playaway View : [Manufactured and distributed by] Findaway World, LLC, 2011)
Hello sun: Quentin the hedgehog longs to see the sun, but the trees in the forest where he lives block his view. So Quentin comes up with a plan -- he'll build a treehouse! But this proves to be a big task for a little hedgehog. With a little determination and some help from his friends, Quentin reaches new heights and finally greets the sun.
I wish I had freckles like Abby: Rosa wants freckles just like her friend Abby. How can she get them? Maybe chocolate pudding will do the trick! How about some mud puddle dots? Big sister's makeup? Rosa comes to realize that she might have something that is just as good as the longed-for freckles.
Princess Justina Albertina: Princess Justina Albertina likes to have her own way. When she doesn't get it, she gets a funny look in her big green eyes and starts to fuss. She causes a ruckus and a rumpus and a horrible hubbub. When this horrid princess declares, "I WANT A PET!" her nanny searches far and wide to find the pet of Princess Justina Albertina's dreams.
Sally Dog Little: When the Littles decide it's time to get a dog, everyone has a specific purpose in mind. But then things go awry, and the formality of the Littles' household threatens to come undone. It's up to Sally Dog to restore order!
Stella the star: Stella's parents are so proud. Her teacher wants her to be the star in the school play. After much anticipation, the adorable Stella wins the hearts of all audiences and makes her parents very proud in this charming story with a surprising finale.
When pigs fly: Ralph's father tells him he can have a new bicycle "when pigs fly." Instead of giving up, Ralph cheerfully tries to get his curly-tailed pals airborne.
Hello sun / [author and illustrator: Hans Wilhelm] (8 min.) -- I wish I had freckles like Abby / [author: Kathryn Heling and Deborah Hembrook ; illustrator: Bonnie Adamson] (3 min.) -- Princess Justina Albertina / [author: Ellen Dee Davidson ; illustrator: Michael Chesworth] (8 min.) -- Sally Dog Little / [author: Bill Richardson ; illustrator: Celine Malepart] (11 min.) -- Stella the star / [author: Mark Shulman ; illustrator: Vincent Nguyen] (6 min.) -- When pigs fly / [author: Valerie Coulman ; illustrator: Roge] (5 min.).
Title from Playaway View label.
Release date supplied by publisher.
Previously released by TumbleBook Library, c2010.
Issued on Playaway View, a dedicated video media player.
Powered by rechargable battery ; container includes one electrical power adapter.
Earphones not required for audio playback.
Keywords: Animals; Pets; Behavior; Dogs; Princesses; Freckles; Schools; Parent and child; Theater; Children's films